Fifty years of the Cleft Centre in Bratislava - Fedeles, J; Janovic, J; Oravkinová, Z; Klímová, I; Fekiacová, D (Acta chirurgiae plasticae, 2004)
In our paper, we would like to present and analyse the activities in the Cleft Centre in Bratislava between 1952 and 2001. We document the gradual development of the complex treatment and the important changes in the usage of the operative techniques and in the primary and secondary operations timing, as well as the application of the new trends in the field of plastic surgery, maxillofacial surgery, anaesthesiology, orthodontics, speech therapy, paediatrics, human genetics and psychology.
Keywords: Plastic Surgery Procedures; stomatochirurgické výkony; Adolescent; rozštěp patra; rozštěp rtu; Infant; kojenec; Humans; Child, Preschool; Cleft Lip; Cleft Palate; Oral Surgical Procedures; Slovakia; lidé; zákroky plastické chirurgie; Child; předškolní dítě; dítě; mladiství; Slovenská republika